Coalition formation in multilateral negotiations with a potential for logrolling: An experimental analysis of negotiators' cognition processes - Marco Lehmann-Waffenschmidt; Livia Reina (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
In the present study we analyse the topic of coalition formation in multi-issue multilateral negotiations under different voting rules when there is the opportunity of logrolling. We have carried out 3 experiments and compare our findings with the standard public choice theory predictions. In the first experiment we have shown that in a situation of 3-issues and 3-parties negotiations with majority rule, most of the subjects behave in a satisficing, not in a optimizing, way. They are found to be subject to a "Zone of Agreement Bias" (ZAB) which induces them to form suboptimal coalitions and to choose Pareto-dominated agreements. Moreover, we find that the cycling problem predicted by public choice theory in most cases does not arise. In experiment 2 we have shown that the adoption of the unanimity, instead of the majority, rule reduced the suboptimizing effect of the ZAB, and produced a much higher rate of optimal agreements. Experiment 3 shows that the results obtained in experiments 1 and 2 hold even when the level of complexity of the negotiation problem increases. To this aim we considered a situation of four-issues and four-parties negotiations under both the majority and the unanimity rule.
Keywords: D72; C91; C92; 330; Koalition; Verhandlungstheorie; Test; Stimmentausch; Kognition